Generation planning for improving reliability of power system in north and central 1 region of Lao PDR - K. Somboukhanh (2018)
© 2017 IEEE. This paper presents a study the generation development plan of Electricité du Laos (EDL) in the north and central 1 region of the Lao people's democratic republic (Lao PDR). This study considered the 12 hydropower development plan projects, which will be connected to the EDL power grid by using the theories of the power flow analysis (voltage, loading, and power loss) and system reliability assessments. The EDL's technical data, including power development plan and the load demand forecast have been used. The DIgSILENT PowerFactory V.15 software is used for analyzing the data in several cases. The analysis results show the transmission line overloading and power loss in the system, which will be used to select the appropriate case for generation planning. The hydropower plant addition and transmission line improvement can cause the reduction of reliability indices and energy not supply. Consequently, the research is the basic analysis of the suitable generation planning of EDL.